Exploring recent advances in carrageenan-based films for sustainable food packaging applications - Thulasidhas Dhilipkumar (22503629) (2025)
The use of non-renewable plastic packaging poses significant environmental challenges. To address these issues, researchers are focused on developing sustainable packaging materials that are environmentally friendly alternatives. The carrageenan (CG), a polysaccharide derived from seaweed, has been processed into a packaging film and studied for food packaging applications due to its distinctive physicochemical properties. CG-based films have garnered attention due to their abundant availability, ability to form films, and overall effectiveness. The current review outlines recent advances in the preparation of CG-based films for various fields of food packaging, such as active, edible, and antimicrobial packaging. Moreover, a brief insight is provided into the effect of additive inclusion on physicochemical, antimicrobial, and antioxidant properties of CG-based films. The suitability of different types of CG, such as kappa (κ), iota (ι), and lambda (λ) for food packaging applications is also discussed by considering their individual film-forming abilities, gel strength, and compatibility with functional additives. The use of CG-based films in food preservation, including their ability to extend the shelf life of fruits, vegetables, meats, and dairy products, is also reviewed. Furthermore, the review addresses the challenges and limitations associated with CG-based films, such as their sensitivity to moisture, mechanical strength, and difficulties in commercial-scale production. The consumer perception and safety aspects related to the use of CG films in food contact applications are also highlighted in the present review. Overall, this review presents a comprehensive overview of CG-based films, covering their preparation, properties, applications, safety, limitations, and future research directions for their development as eco-friendly food packaging materials. Other Information Published in: European Food Research and Technology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00217-025-04835-6